Alkoxido-bridged binuclear copper(ii) complexes derived from aminoalcohols – useful building blocks in designing coordination polymers with a rich structural variety. Issue 26 (26th June 2017) - Mocanu, Teodora; Tudor, Violeta; Andruh, Marius
Abstract : Binuclear alkoxido-bridged species act as robust nodes in designing 1-D, 2-D, and 3-D coordination polymers. This paper reviews the chemistry of coordination polymers constructed from alkoxido-bridged binuclear copper(ii ) nodes and a rich variety of spacers. Abstract : The reactions of copper(ii ) salts with aminoalcohols frequently afford alkoxido-bridged dimers. Neutral ( e.g. bis(4-pyridyl) derivatives) or anionic divergent ligands ( e.g. polycarboxylate anions, polycyanido-metallates) are employed as spacers. In this paper, a rich variety of structures are reviewed, emphasizing the role played by the denticity of the aminoalcohols and of the linkers, as well as by the accompanying anions, in the network topology. The involvement of coordinative and non-covalent bonds (π–π stacking, argentophilic/aurophilic, π⋯Hg interactions, hydrogen bonds) in sustaining the solid-state architectures is also discussed.